2013
DOI: 10.1177/0004563213490289
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected increased ferritin concentration in patients with anorexia nervosa

Abstract: Analytical validity studies are important at an early stage and we encourage others to validate the new formula in different population samples. However, clinical validity and utility studies are of additional importance, as it is necessary to evaluate an eventual improvement of therapeutic management and costeffectiveness of a new approach. 5 A study evaluating the performance of the new formula compared to beta-quantification in a sample of a clinically welldefined cohort is also needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…There was a significant increase in the iron storage ferritin in group 2, we suggested that the higher serum ferritin concentrations represent an increased state of inflammation, as it acts as an acute phase reactant [20]; furthermore, ferritin has non-storage roles within the body, such as protection from oxidative damage [21]. Indeed, its synthesis is increased in response to oxidative stress [22] which was stated to occur in chronic kidney disease [23], and it is, therefore, a non-reliable indicator of iron disturbance [20].…”
Section: Disscussionmentioning
confidence: 84%
“…There was a significant increase in the iron storage ferritin in group 2, we suggested that the higher serum ferritin concentrations represent an increased state of inflammation, as it acts as an acute phase reactant [20]; furthermore, ferritin has non-storage roles within the body, such as protection from oxidative damage [21]. Indeed, its synthesis is increased in response to oxidative stress [22] which was stated to occur in chronic kidney disease [23], and it is, therefore, a non-reliable indicator of iron disturbance [20].…”
Section: Disscussionmentioning
confidence: 84%
“…Elevated ferritin concentrations have previously been reported in AN (8,9,10,11,12,13,14,15,16). Although iron insufficiency from inadequate oral intake is common, iron metabolism is believed to be intact despite both high and low ferritin levels that can occur with AN (14).…”
Section: Discussionmentioning
confidence: 96%
“…Although these results are not consensual in the literature, 17 several authors have reported increased ferritin values in AN patients, with a tendency to normalization associated with weight recovery. 15,16,[28][29][30] Ferritin is frequently used to evaluate Iron stores, but may be elevated in situations such as liver damage, neoplasia, infection, and inflammation. Thus, it is difficult to interpret its elevation in AN patients, and, currently, its pathophysiological mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%